The Prevalence of Climacturia in Patients after Radical Prostatectomy: A Systematic Review - João Vítor Ferrão; Alice Scalzilli Becker; Gustavo Konopka; Gustavo Bangemann; Thiago Oliboni; Nilson Marquardt Filho; Carlos Teodósio Da Ros; Gustavo Franco Carvalhal (International Brazilian Journal of Urology)
ABSTRACT Purpose: Prostate Cancer (PCa) is the most common non-cutaneous cancer in males, and Radical Prostatectomy (RP) is among the primary treatments for this condition. Our study aims to investigate the prevalence of climacturia (urine leakage at the moment of the climax), a potential post-RP change related to orgasm. Material and Methods: A systematic review was conducted following PRISMA guidelines and registered on the PROSPERO platform. The search was performed using MEDLINE via PubMed. Results: Thirteen studies met the inclusion criteria and were described separately. Within these studies, 5,208 patients were evaluated, among which 1,417 cases of climacturia were identified, with a prevalence of 27.2%. When we analyzed the robot-assisted radical prostatectomy (RARP) subgroup, the prevalence of climacturia was 5.7% vs 1.8% the open radical prostatectomy (ORP) subgroup. Conclusion: Climacturia is a frequently underestimated complication by urologists. Given its significant impact on quality of life, it warrants greater attention from specialists following RP.